O sujeito estudante da educação de jovens e adultos: uma análise histórico-discursiva - Nascimento, Rebeca Barbosa (2017)
With relevant contributions in several areas of knowledge, Michel Foucault provided, in his work, important reflections on the subjects and their processes of historical constitution within the relations established between power, truth and knowledge. Starting from Foucault's notion of subject, the present work constitutes an investigation of historical-discursive processes that discourses the formation of the student in the Young and Adult Education Program (EJA). To do so, initially, a brief historical-documental overview was given on the education movements for young people and adults in Brazil, reflecting on the constitution of the program in its relation with the public to which it is directed. Subsequently, the process of analysis was constructed based on The Archeology of Knowledge, and it is therefore a careful reading of the possible regularities found in the linguistic materiality of chapter 1 of the Portuguese Language segment of the program's textbook . The identification of possible regularities is followed by a characterization of the surfaces of emergence of possible speeches and, finally, the possibilities and interdictions that delimit the margins of constitution of the student subject of the EJA Program through the exteriorities are demarcated.